2007
DOI: 10.4049/jimmunol.179.11.7840
|View full text |Cite
|
Sign up to set email alerts
|

Heme Oxygenase-1 Inhibits the Expression of Adhesion Molecules Associated with Endothelial Cell Activation via Inhibition of NF-κB RelA Phosphorylation at Serine 276

Abstract: Heme oxygenase-1 (HO-1; encoded by the Hmox1 gene) catalyzes the degradation of free heme into biliverdin, via a reaction that releases iron (Fe) and carbon monoxide. We report that HO-1 down-regulates the proinflammatory phenotype associated with endothelial cell (EC) activation by reducing intracellular nonprotein-bound Fe (labile Fe). EC isolated from Hmox1−/− mice have higher levels of intracellular labile Fe and reactive oxygen species (ROS) as compared with EC isolated from Hmox1+/+ mice. Basal and TNF-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
93
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(106 citation statements)
references
References 60 publications
(88 reference statements)
12
93
0
1
Order By: Relevance
“…The PI3K/Akt pathway elicits a survival signal against apoptotic insults 26 Bcl-2 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 31 ; Production of iron limits transcription of proinflammatory genes by inhibiting phosphorylation of NF-κB p65 32 ; Biliverdin may also serve as an antioxidant 29 . In vitro studies using neuronal cultures have shown that HO-1 protects neurons against oxidative injury 33 .…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K/Akt pathway elicits a survival signal against apoptotic insults 26 Bcl-2 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 31 ; Production of iron limits transcription of proinflammatory genes by inhibiting phosphorylation of NF-κB p65 32 ; Biliverdin may also serve as an antioxidant 29 . In vitro studies using neuronal cultures have shown that HO-1 protects neurons against oxidative injury 33 .…”
Section: Discussionmentioning
confidence: 99%
“…7,8 In order to assess if ARE-driven HO-1 expression can have antiinflammatory effects in endothelial cells, we first examined its effect on NF-kB activation assessed by the activation of the NF-kB-regulated luciferase-reporter construct. To this end, cells were transduced with either an empty lentiviral control vector having only the phosphoglycerate kinase (PGK) promoter but no transgene, or 2 Â GCLM-HO-1 vector together with the NFkB-luciferase-reporter construct.…”
Section: Lentiviral Transduction Of Are-ho-1 Decreases the Induction mentioning
confidence: 99%
“…In endothelial cells, adenoviral overexpression of HO-1 has been shown to inhibit tumor necrosis factor (TNF)-a-induced activation of nuclear factor (NF)-kB and vascular cell adhesion molecule-1 (VCAM-1) expression. 7,8 For an optimal therapeutic response, it would be beneficial if the transgene expression could be regulated in order to turn the gene expression on and off when needed. This can be accomplished through the use of promoters that can be activated by orally administered drugs, such as tetracycline.…”
Section: Introductionmentioning
confidence: 99%
“…Frequent loss of FHIT in tumors is well documented. 5,9,16,29 Of equal significance, FHIT inactivation occurs early in the process of carcinogenesis, particularly in lung cancer, 18,30 suggesting that loss of this gene may facilitate acquisition of the additional alterations required for cell transformation.…”
Section: Introductionmentioning
confidence: 99%
“…20,32 However, expression of a catalytically inactive Hmox1 mutant promotes cell survival after stress as well as the wild type protein, suggesting that Hmox1 cytoprotection functions through an independent, yet to be elucidated mechanism. 28,33 Early events that occur after Hmox1 expression include increased cell proliferative capacity, 29,34 decreased cell adhesion, 30,35 increased migration potential, 31,35,36 and evasion of apoptosis. 32,37 It follows that HMOX1 overexpression is detected in many cancers, including prostate malignancies, melanoma, glioma, adenocarcinoma, and others.…”
Section: Introductionmentioning
confidence: 99%